2010
DOI: 10.1002/cncr.25146
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the esophagus and esophagogastric junction

Abstract: request of the AJCC, worldwide data from 3 continents were assembled to develop data-driven, harmonized esophageal staging for the seventh edition of the AJCC/UICC cancer staging manuals. METHODS: All-cause mortality among 4627 patients with esophageal and esophagogastric junction cancer who underwent surgery alone (no preoperative or postoperative adjuvant therapy) was analyzed by using novel random forest methodology to produce stage groups for which survival was monotonically decreasing, distinctive, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(165 citation statements)
references
References 97 publications
2
163
0
Order By: Relevance
“…Therefore, small cardia cancer within 5 cm but apart from the EGJ is classified as gastric cancer, but it can be staged according to esophageal cancer after it grows enough to reach to the EGJ. This esophageal cancer staging came from an assembled worldwide database from three continents to overcome the previous esophageal cancer staging system which had problems of empiric stage grouping and lack of harmonization with stomach cancer [38,39,40]. …”
Section: Uicc/ajcc Tnm Staging Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, small cardia cancer within 5 cm but apart from the EGJ is classified as gastric cancer, but it can be staged according to esophageal cancer after it grows enough to reach to the EGJ. This esophageal cancer staging came from an assembled worldwide database from three continents to overcome the previous esophageal cancer staging system which had problems of empiric stage grouping and lack of harmonization with stomach cancer [38,39,40]. …”
Section: Uicc/ajcc Tnm Staging Systemmentioning
confidence: 99%
“…The extremely different incidence of esophageal adenocarcinoma, EGJ cancer, and gastric cancer in Western and Eastern countries has limited the well-designed comparative research. The reference data for esophageal cancer staging were collected through the Worldwide Esophageal Cancer Collaboration in which there were only two Eastern hospitals among the 48 participating institutions and about 65% of the data used for the analysis was collected before 2000 [38,39,40]. Moreover, the Japanese population that represents the Eastern population usually has a much shorter length of the lesser curvature (about 15-20 cm) than Americans, who represent the Western population [46].…”
Section: Uicc/ajcc Tnm Staging Systemmentioning
confidence: 99%
“…In the latest revision of the AJCC Staging Manual, T4 tumors were divided into resectable tumors (T4a) and unresectable (T4b). Those tumors invading pleura, pericardium and diaphragm are considered resectable and those invading other structures such as the trachea and aorta are considered unresectable [1,26]. Image 3.…”
Section: Determining the T Stagementioning
confidence: 99%
“…Decreased accuracy and understaging has been reported when a biliary stent is present. Intraductal ultrasound (IDUS) is yet another method of visualizing ampullary tumors by use of a high-frequency ultrasound probe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) inserted into the bile duct during ERCP. Various studies have shown superior T staging for IDUS compared to EUS [56,58,59], with overall accuracy for tumor staging ranging between 78-88% for IDUS.…”
Section: Staging Of Ampullary Tumorsmentioning
confidence: 99%
“…Finally, the principle of assuring homogeneity within groups guided both the amalgamation and segmentation of cancer characteristics between adjacent groups to arrive at the final stage groupings [3][4][5].…”
Section: Introductionmentioning
confidence: 99%